The Use of Nutritional Supplements in Dressage and Eventing Horses. (June 2014) - Agar, C; Gemmill, R; Hollands, T; Freeman, S
Abstract : Introduction: Selecting the appropriate nutritional supplements for performance horses is difficult, due to significant gaps in the current scientific evidence. Our hypothesis was that nutritional supplements are chosen based on owner's perception of discipline specific health and performance problems. Methods: A mixed methods (open and closed questions) online questionnaire was distributed through British Eventing and Dressage websites, to collect data on demographics of owners and their horses, supplements used, and their opinion on health and performance problems in their discipline, and in their own horses. Data was evaluated using descriptive analysis and Sign and Fisher's exact tests for quantitative data, and thematic analysis for qualitative data. Results: 599 responses met the inclusion criteria, of which 441 were or had competed in dressage, and 158 in eventing (unaffiliated novice to affiliated advanced levels). Participants had been riding for 26.4 (3–60) (mean (range)) years, currently competed 1.2 (0–10) horses, and used 2 (0–12) supplements in their top horse. Participants ranked the most important health and performance issues as (1) Energy and behaviour, (2) Lameness, (3) Back and muscle problems for dressage, and (1) Lameness, (2) Energy and behaviour, (3) Stamina and fitness for eventing horses. The most common reason supplements were used in individual horses were (1) Joints and mobility, (2) Behavioural problems for dressage, and (1) Electrolytes, (2) Joints and mobility for eventing. Conclusions: There was discrepancy between participants' opinions of the main health and performance problems within their discipline, and their reasons for using supplements. Ethical Animal Research: The study was approved by the School of Veterinary Medicine and Science Ethics Committee at University of Nottingham.Sources of funding: School of Veterinary Medicine and Science, University of Nottingham.Competing interests: Teresa Hollands is employed by Dodson and Horrell Ltd.